Implementasi Bimbingan Kelompok dengan Teknik Permainan Simulasi Berbasis Kearifan Lokal dalam Pengembangan Pribadi-Sosial Siswa - Henny Indreswari; Achmad Miftachul ‘Ilmi; Shabrina Muyassirotul ‘Aliyah; Khairul Bariyyah (JKI (Jurnal Konseling Indonesia), 2021)
The development of the 4.0 industrial revolution era can cause various personal-social problems in the younger generation. Various facts show the low ability of junior high school students in personal-social development. The provision of personal-social guidance services can be provided by counselors as a preventive effort for students in dealing with problems related to adjustment, physical care, spirituality, dealing with conflict, and association. The implementation of group guidance services using simulation game techniques using traditional games is predicted to be able to support students' personal-social development. This study aims to describe the implementation of group guidance services using simulation game techniques based on local wisdom to support the development of personal-social aspects of junior high school students. The method used in this research is literature review. Based on the literature review obtained, several traditional games were found that could be used, including bakiak, dakon, betewah, moving star, engklek, leng kali leng, Tuan dosi, jilo-jilo, gate-gate, buton, babubutaan, torturing, sondah, and gobak sodor. The use of traditional games is effective as a preventive effort in dealing with personal-social problems, including increasing cooperation, increasing interpersonal communication, reducing aggressiveness, increasing prosocial behavior, increasing motivation to learn, and awareness of responsibility.